Moderating Role of Tenure in an Organization and Work Engagement on Organization Citizenship Behaviour and Task Performance - Honnamane, Preeti S.; Sreekanth, K.; Girish, G. P. (International Review of Management and Marketing, 2024)
In this study we explore moderating role of tenure in an organization and work engagement on organization citizenship behaviour and task performance among employees in top 10 IT companies in Bangalore as catalogued by the National Stock Exchange of India. Primary data were collected via an online survey administered to 224 employees between April and September 2022. Utilizing Partial Least Squares Structural Equation Modelling, the analysis reveals that while extended tenure fosters deeper role comprehension and stronger interpersonal bonds its impact on task performance is minimal and its effect on organization citizenship behaviour is negligible. The study underscores the importance of supportive work environment and calls for future research on industry-specific factors that could further shape the dynamics of tenure and engagement.